Advertisement Remove all ads

Solve by Method of Variation of Parameters : ( D 2 − 6 D + 9 ) Y = E 3 X X 2 - Applied Mathematics 2

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Sum

Solve by method of variation of parameters :`(D^2-6D+9)y=e^(3x)/x^2`

Advertisement Remove all ads

Solution

`(D^2-6D+9)y=e^(3x)/x^2`
For complementary solution ,
𝒇(𝑫)=𝟎

`therefore(D^2-6D+9)=0`

Roots are : D = 3 , 3 Real roots but repeatative.
The complementary solution of given diff. eqn is ,

`therefore y_c=(c_1+xc_2)e^(3x)`

For particular solution ,
By method of variation of parameters,

`y_p=y_1p_1+y_2p_2`

where `p_1=int(-y_2X)/wdx`

`p_2=int(-y_1X)/wdx`

`w=|(y_1,y_2),(y'_1,y'_2)|`

`w=|(e^(3x),xe^(3x)),(3e^(3x),e^(3x)+3xe^(3x))|=e^(6x)`

`p_1=int(-y_2X)/wdx=int(xe^(3x))/e^(6x).e^(3x)/x^2dx=int(-1)/xdx=-logx`

`p_2=int(-y_1X)/wdx=int(e^(3x))/e^(6x).e^(3x)/x^2dx=int(1)/x^2dx=(-1)/x`

The particular integral of given diff. eqn is given by,

`thereforey_p=-e^(3x)logx-e^(3x)=-e^(3x)(logx+1)`

The general solution of given diff. eqn is given by ,

`y_g=y_c+y_p=(c_1+xc_2)e^(3x)=-e^(3x)(logx+1)`

Concept: Method of Variation of Parameters
  Is there an error in this question or solution?
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×